Patrimônios (in) visíveis experiências museológicas na comunidade de Fortalezinha/Pará - SOUZA, Flávia Suanny Santana de (2021)
This research is a reflection about museology actions developed at the community of Fortalezinha (PA) by the project “(In) Visible Patrimonies – The documental photography as process of artistic investigation”, which the final result was the exhibition (In) Visible Patrimonies – Fortalezinha. The project consisted in research/action oh college extension made during the years of 2015/2016 at the referred Village and was the winner of the Proex of Art and Culture Award. The discussion to which it links thinks patrimony beyond tipping and register from the competent agencies, enlightening the self-determination, the idea of the own social groups about what could be considered patrimony according their social experience, setting precedents for all material and immaterial expressions. Photography as tool of visual register of those patrimonies elected by the community, however its role in this project goes beyond the mere documental register, because it is thought as a way of safeguard of these patrimonies. For such registers the experience was essential in and with the community, taking part of the daily life of locals, as well as recordings of their speeches through interviews and chatting, to look for the roots of what was to be photographed.